2020
DOI: 10.12982/cmujns.2020.0049
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Acid Tolerant Purple Nonsulfur Bacteria for Application in Agriculture

Abstract: To screen acid tolerant purple nonsulfur bacteria (PNSB) isolated from peat swamp forests for their abilities to produce plant growth promoting substances (aminolevulinic acid: ALA, siderophores, indole-3-acetic acid: IAA) and also release ammonium from N2 fixation. Among 10 PNSB isolates grown in basic isolation medium (BIM), pH 4.5 found that strain KKSSR91 was the most effective to release ALA and siderophores under microaerobic light conditions; while strain KTPWG11 exhibited highest production of sideroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Two other R. palustris strains, GJ-22 and KL9, have also been reported to yield 30-52 mg/L IAA in the presence of tryptophan [73,101]. It was reported that R. palustris KKSSR91, which secreted IAA (29.58 mg/L) in the presence of 3 mM tryptophan, was able to reduce the phytotoxic effects of acid on kidney bean plants [102]. Rhodobacter capsulatus PS-2, which was isolated from paddy soil, was capable of producing a large amount of IAA (197.44 ± 5.92 mg/L) in an optimal medium containing 0.3% tryptophan.…”
Section: Indole-3-acetic Acid (Iaa) Production By Pnsbmentioning
confidence: 99%
“…Two other R. palustris strains, GJ-22 and KL9, have also been reported to yield 30-52 mg/L IAA in the presence of tryptophan [73,101]. It was reported that R. palustris KKSSR91, which secreted IAA (29.58 mg/L) in the presence of 3 mM tryptophan, was able to reduce the phytotoxic effects of acid on kidney bean plants [102]. Rhodobacter capsulatus PS-2, which was isolated from paddy soil, was capable of producing a large amount of IAA (197.44 ± 5.92 mg/L) in an optimal medium containing 0.3% tryptophan.…”
Section: Indole-3-acetic Acid (Iaa) Production By Pnsbmentioning
confidence: 99%